Comparison of Efficacy of Topical Permethrin vs Oral Ivermectin in Scabies - Kalsoom Aslam, Sarah Riaz Khan, Amna Begum, Asghar Ali Memon, Farooq Azam Khan, Hafsa Usman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Sarcoptes scabiei var. homoinis is the common cause of scabies. A number of ectoparasites and endoparasites can be effectively combated using the antiparasitic drug ivermectin orally. Permethrin is a pesticide when administered topically, destroys the scabies causing mite and their eggs. Objective: To evaluate the effectiveness of topical permethrin and oral ivermectin in the management of scabies. Methods: The current study was carried out at the department of dermatology, Kuwait Teaching Hospital Peshawar for a period of six months from January 2023 to June 2023. After the informed consent, the hundred recruited patients were divided into two groups for the randomized controlled experiment. On day zero, all the 50 patients in group B received topical permethrin 5% treatment, whereas all 50 cases in group A received oral tab Ivermectin at a dosage of 200 mcg/kg. For comparison, clinical and itch grading scores were used as tools. SPSS version 23 was used for statistical analysis. Results: Patients who got oral Ivermectin had a mean age of 39.79 ±11.48 years, whereas those who received permethrin 5% had a mean age of 40.57±11.25 years. There were 26 (52 %) cases of effectiveness (p value<0.05) in the Ivermectin group compared to 43 (86%) cases in the permethrin 5% group. Permethrin (5%) continued to be more effective. Conclusion: Permethrin 5% compared to Ivermectin can be used to treat scabies in order to increase cure rates against scabies. Keywords: Efficacy; Topical permethrin; Oral Ivermectin; Scabies